The Art of Anti-Snake Venom Administration in Snakebite Grade III Following Viper Snakebite in Developing Country: A Case Report - Hapsari Kinanti; Agung Kusumanegara (Jurnal Kedokteran Diponegoro, 2024)
Snakebite remains a prior Neglected Tropical Disease in the World, especially in South-East Asia. There were many diversities in the management of snake bites based on the different levels of clinician experience. Anti-snake venom remains the mainstay treatment in venomous snakebites, meanwhile, the distribution of anti-snake venom is very sparse. Snakebite is time-limited and could be a life-threatening event. This case report described a delayed anti-snake venom administration in snakebite grade III following a viper snake bite. Tight observation including clinical manifestation and laboratory tests is the foremost thing to do in managing snakebite, due to its unpredictable clinical manifestation. Anti-snake venom dosage must be decided based on the progress of clinical manifestation and laboratory results.